PENERIMAAN SISWA BARU DI SDN 11 PENDOPO - Zulfan Afendi; Sumarsih Sumarsih (UNIVERSITAS BENGKULU, 2019)
Abstract : the purpose of this study is to describe in depth the management of new student admission atau elementary school number 11 Pendopo Empat Lawang Regency. This research uses descriptive qualitative research method. The subjects of the study were principals, vice principals, teachers, supervisor and students. Data collection is done through interview, observation, and documentation. Data analysis using qualitative analysis technique. The result of the research in the form of conclusion is in accordance with the policy set by the Ministry of Education and Culture of the Republic of Indonesia, and adjusted by the service in the district of Empat Lawang, and adjusted again by the school. Keyword: New Student, Admisions